2002
DOI: 10.1562/0031-8655(2002)076<0530:cotpeo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Photodynamic Effect of Exogenous Photoprotoporphyrin and Protoporphyrin IX on PAM 212 Murine Keratinocytes¶

Abstract: A comparative study of the cellular photosensitizing properties of protoporphyrin IX (PpIX) and photoprotoporphyrin (Ppp) was carried out in the transformed murine keratinocyte cell line, PAM 212. Time-course fluorescence studies were performed to determine the rate of uptake by cells together with fluorescence microscopy. The sensitized cells were laser irradiated with a range of light doses at 635 or 670 nm to determine the phototoxicity of the two compounds and to investigate their relative fluorescence pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…having a cross-section (σ 2PE ) of the order of 10 −50 cm 4 s, photon, competes with a more probable one-photon transition, i.e. cross-section (σ 1PE ) of the order of 10 −15 cm 2 photon [25]. The probabilities of the one-photon ( P 1PE ) and the two-photon ( P 2PE ) excitation processes can be described as…”
Section: Resultsmentioning
confidence: 99%
“…having a cross-section (σ 2PE ) of the order of 10 −50 cm 4 s, photon, competes with a more probable one-photon transition, i.e. cross-section (σ 1PE ) of the order of 10 −15 cm 2 photon [25]. The probabilities of the one-photon ( P 1PE ) and the two-photon ( P 2PE ) excitation processes can be described as…”
Section: Resultsmentioning
confidence: 99%
“…Exogenous administration of ALA and its esters (8) practically bypasses the negative feedback control exerted by heme on enzymatic ALA synthesis, thus making ALA a very efficient PpIX prodrug widely used for clinical PDT, following either topical or systemic application (9). Nevertheless it was previously shown that exogenous application of PpIX to cells resulted in very efficient photocytotoxicity (10). One serious limitation in the exogenous use of PpIX much alike many other PSs is its low water solubility, and consequently the difficulty in preparing pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the initial photosensitizer absorption coefficient used as initial condition in the photochemical model (5)(6)(7)(8)(9)(10)(11) was obtained by means of equation 4, taking into account the previously obtained inhomogeneous photosensitizer concentration and an absorption cross-section of the PpIX, psa σ = 0.37·10 -15 cm 2 at 635 nm, which was derived from a study of the cellular photosensitizing properties of PpIX carried out in a transformed murine keratinocyte cell line 16 . Due to the fact that MAL is a derivative of 5-aminolevulinic acid, the relaxation time from singlet excited state to ground state S 1 to S 0 was set to 7.4 ns as reported earlier from fluorescence measurements in cells incubated with 5-aminolevulinic acid induced PpIX 17 .…”
Section: Resultsmentioning
confidence: 99%